Vaccine hesitancy or hesitancies? A latent class analysis of pediatric patients' parents - Don E. Willis; Marie‐Rachelle Narcisse; Laura James; James P. Selig; Mohammed Ason; Aaron J. Scott; Lawrence E. Cornett; Pearl A. McElfish (Clinical and Translational Science)
Abstract Vaccine hesitancy is an attitude of indecision toward vaccination that is related to but not determinative of vaccination behaviors. Although theories of vaccine hesitancy emphasize it is often vaccine‐specific, we do not know the extent to which this is true across sociodemographic groups. In this study, we asked: What latent classes of vaccine hesitancy might exist when examining parents' attitudes toward vaccines in general and COVID‐19 and human papillomavirus (HPV) vaccination specifically? Which sociodemographic, health access, and health‐related variables are predictive of membership in those classes? To answer those questions, we analyze online survey data from parents of pediatric patients recruited through eight clinics within the University of Arkansas for Medical Sciences Rural Research Network. Data were collected between September 16, 2022 and December 6, 2022. Latent class analysis revealed three underlying classes of vaccine hesitancy, or hesitancies: The “Selectively Hesitant,” the “COVID‐Centric Hesitant,” and the “Pervasively Hesitant.” Significant predictors of class membership were age, education, health insurance status, and usual source of care. Vaccine hesitancy may be specific to certain vaccines for some parents and more generalized for others. The distinct classes of vaccine hesitancy revealed in this study suggest the need for distinct approaches to addressing vaccine hesitancy depending on the population.